Lactic acid bacteria secrete metabolites retaining anti-inflammatory properties after intestinal transport - Ménard, S (Copyright 2004 by Gut, 2004)
Background: Probiotic bacteria have a beneficial effect on intestinal inflammation. In this study, we have examined the effect of lactic acid and commensal Gram positive (+) bacteria conditioned media (CM) on tumour necrosis factor α (TNF-α) release and the mechanisms involved. Methods: Lipopolysaccharide (LPS) induced TNF-α secretion by peripheral blood mononuclear cells or the THP-1 cell line was monitored in the presence or absence of bacteria CM obtained from two probiotic strains, Bifidobacterium breve (Bb) and Streptococcus thermophilus (St), and three commensal bacterial strains (Bifidobacterium bifidum, Ruminococcus gnavus, and unidentified Streptococcus). Bb and St bacteria CM were allowed to cross filter grown intestinal epithelial cell monolayers (HT29-19A) to assess intestinal transport of active bacterial products. These products were characterised and their effect on LPS binding to THP-1 cells and nuclear factor κB (NFκB) activation assessed. Results: Dose dependent inhibition of LPS induced TNF-α secretion was noted for both probiotic bacteria CM (64% and 71% inhibition for Bb and St, respectively) and to a lesser extent commensal bacteria CM (21–32% inhibition). Active products from Bb and St were resistant to digestive enzymes and had a molecular mass <3000 Da. Their inhibitory effect was preserved after transepithelial transport across intestinal cell monolayers, mainly in inflammatory conditions. LPS-FITC binding to THP-1 cells and NFκB activation were significantly inhibited by Bb and St CM. Conclusion: B breve and S thermophilus release metabolites exerting an anti-TNF-α effect capable of crossing the intestinal barrier. Commensal bacteria also display a TNF-α inhibitory capacity but to a lesser extent. These results underline the beneficial effect of commensal bacteria in intestinal homeostasis and may explain the role of some probiotic bacteria in alleviating digestive inflammation.